PRELIMINARY MONITORING OF WATER QUALITY AT BANTURUNG VILLAGE, BUKIT BATU DISTRICT, PALANGKA RAYA CITY - Stevin Carolius Angga; Sudarman Rahman; Erwin Prasetya Toepak; Ferry Patrix (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
Water is a vital necessity for human and living things in general. It is undeniable that the decline in water quality today is the result of human activities that overexploit the environment. People's lifestyles that pay less attention to environmental aspects such as throwing garbage out of place, disposing of hazardous waste, and changing the function of forest areas that can increase the potential for erosion and often cause sedimentation at the bottom of the waters have a negative impact both directly and indirectly on the natural environment, especially water sources. High rate of forest degradation and deforestation has a significant impact on changes and decreases in water quality. In this study, water quality monitoring was conducted using several parameters as an initial step to understand the condition at the Dam and Clean Water Facility in Banturung Village, Bukit Batu District, Palangka Raya City. The results obtained from the analyzed parameters include odorless, pH 5.9, turbidity 1.0 NTU, temperature 28.1 °C, color 3.63 TCU, total dissolved solids (TDS) 10.2 mg/L, nitrate (NO3-) 0.608 mg/L, nitrite (NO2-) 0.002 mg/L, iron (Fe) 0.038 mg/L, and manganese (Mn) 0.006 mg/L.